THE EFFECT OF FLOW SUGAR IN DIFFERENT LEVELS ON THE QUALITY OF CHEMISTRY CHEMICAL - Syuhada, Wahyuni; Hafid, Harapin; Amiluddin, Amiluddin (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2020)
This study aimed to discover the effect of the addition of different levels of palm sugar on the chemical quality of jerked beef. The jerked beef was made of Bali beef that was given salt, seasoning, and palm sugar in different concentration 10%, 20%, 30%, and 40%. Data were processed using multiple sidik analysis based on Random Complete Design with 4 treatments and 3 repetitions. The observed variables were water content, protein content, fat content, and ash content. The result showed that the adding of palm sugar on the milled jerked beef really affected (p<0.01) the water content of the beef jerked. In this case, the adding of 10% palm sugar content and 20% water content was higher than the adding of 30% and 40%, each 40.85%, and 32.92% compared to 32.54% and 28.48%. This is far different from the treatment (p<0.05) on the fat content, each 8.91%, 8.80%, 7.16%, and 7.74% and it did not really affect (p<0.05) the jerked beef protein content, each about 47.22%, 47.67%, 48.83%, and 53.30%. Further, it did not really affect the ash content of the jerked beef. In conclusion, a good quality caprice of milled jerked beef was found on jerked beef with 40% adding of palm sugar because it contains high protein and low-fat content.Â Â